DISCOURSE AT THE DINING TABLE: FOOD, RITUAL SPEECH, AND CONFLICT RESOLUTION IN MINANGKABAU SOCIETY - Tiara, Inoki Ulma; Azri, Debi Adinda; Zulfi, Raihan M. (ppjbsip, 2025)
This study investigates the role of traditional food and ritual language in the conflict resolution practices of Minangkabau communities in West Sumatra. Using a qualitative ethnographic approach, data were collected through participatory observation, indepth interviews, and document analysis in two Minangkabau nagari (villages). The research highlights how communal feasts, traditional speech (pasambahan), and collective cooking serve as discursive tools that reduce tension, rebuild trust, and symbolically restore social harmony. Culinary rituals, especially involving rendang and gulai, are deeply embedded with meanings that reflect societal structure, cooperation, and reconciliation. Conflict resolution is thus mediated not only through customary institutions but also through symbolic discourse prayers, proverbs, and performative speech acts during meals. By reframing food as a medium of discourse, the study reveals that dining together operates as a social narrative that transforms former adversaries into collaborative participants in peace-building. This paper contributes to discourse analysis by demonstrating how language, ritual, and material culture intersect to manage conflict in a non-coercive and culturally embedded way. The findings suggest that discourse practices surrounding food blessing formulas, inclusive metaphors, and egalitarian seating patterns play a critical role in re-categorizing social identities and diffusing intergroup hostility. As such, peace emerges not only from dialogue but from embodied, shared experiences reinforced through culturally meaningful discourse. This study invites future research on culinary discourse as a communicative strategy in post-conflict reconciliation across diverse cultures.